Bioactivity evaluation of Polygonum minus and identification of synergistic phytochemicals with 5-fluorouracil for colon cancer treatment - Yang, Zhongming; Yang, Zhongguo; Abu Bakar, Md Zuki; Deng, Xi (Elsevier, 2025)
Polygonum minus Hubs (PM), a fragrant herb widely utilized in culinary practices and traditional medicine, possesses various bioactivity that remain underexplored, particularly as synergistic agents for chemotherapies. This study evaluated the antioxidant activity, hemolytic activity, toxicity, and cytotoxicity of PM extracts and their synergy with 5-fluorouracil (5-FU) in colon cancer (CC) treatment. Results showed that methanol stem extract (PM-S-M) had the highest antioxidant activity, and most extracts had low hemolytic activity, except for hexane (PM-L-H) and dichloromethane (PM-L-D) leaf extracts. Toxicity tests classified PM-L-H as low-toxic, PM-L-D as moderate-toxic, and others as non-toxic. Notably, PM-L-H exhibited strong anti-CC effects by inhibiting the viability of CC cells. Subsequently, PM-L-H was further combined with 5-FU for CC treatment. It showed a synergistic effect with 5-FU in inhibiting CC cell growth, as validated by a series of in vitro assays, including cell morphology, AO/PI double staining, colony formation, cell apoptosis, cell cycle, cell migration, and spheroid growth analyses. Network pharmacology and molecular docking screened the key bioactive compounds of PM-L-H against CC, including 1-dodecanol and dotriacontane, and identified the key pathways involved in the synergistic action of PM-L-H and 5-FU against CC, such as neuroactive ligand-receptor interaction, serotonergic synapse, and neurodegeneration-related pathways. Due to their excellent safety profile, 1-dodecanol and dotriacontane deserve further investigation as potential synergists of 5-FU. Therefore, PM-S-M with strong antioxidant properties, low hemolytic activity, and no toxicity holds promise in food supplements, cosmetics, and pharmaceuticals. Meanwhile, 1-dodecanol and dotriacontane synergistically enhanced the efficacy of 5-FU against CC, offering a novel strategy for optimizing CC treatment.